A Global Phosphorylation Atlas of Proteins Within Pathological Site of Rotator Cuff Tendinopathy - Wang, Yezhou; Zhang, Jiawei; Lin, Yuan; Cheng, Shi; Wang, Duanyang; Rao, Man; Jiang, Yuheng; Huang, Xiang; Chen, Ruijing; Xie, Yong; Yin, Pengbin; Cheng, Biao (Frontiers in Molecular Biosciences, 2022)
Rotator cuff tendinopathy (RCT) is the most common cause of shoulder pain, therefore posing an important clinical problem. Understanding the mechanism and biochemical changes of RCT would be of crucial importance and pave the path to targeting novel and effective therapeutic strategies in translational perspectives and clinical practices. Phosphorylation, as one of the most important and well-studied post-translational modifications, is tightly associated with protein activity and protein functional regulation. Here in this study, we generated a global protein phosphorylation atlas within the pathological site of human RCT patients. By using Tandem Mass Tag (TMT) labeling combined with mass spectrometry, an average of 7,741 phosphorylation sites (p-sites) and 3,026 proteins were identified. Compared with their normal counterparts, 1,668 p-sites in 706 proteins were identified as upregulated, while 73 p-sites in 57 proteins were downregulated. GO enrichment analyses have shown that majority of proteins with upregulated p-sites functioned in neutrophil-mediated immunity whereas downregulated p-sites are mainly involved in muscle development. Furthermore, pathway analysis identified NF-κB–related TNF signaling pathway and protein kinase C alpha type (PKCα)–related Wnt signaling pathway were associated with RCT pathology. At last, a weighted kinase-site phosphorylation network was built to identify potentially core kinase, from which serine/threonine-protein kinase 39 (STLK3) and mammalian STE20-like protein kinase 1 (MST1) were proposed to be positively correlated with the activation of Wnt pathway.